A comprehensive analysis of corporate internet reporting practice in Malaysia - Turmin, Siti Zaidah; Abdul Hamid, Fatima; Mohamad Ghazali, Nazli Anum (Medwell Journals, 2016)
Through Corporate Internet Reporting (CIR), a company can provide the traditional annual report with additional financial and non-financial information in multiple formats on the corporate website. CIR is an important channel to present information to the stakeholders and considered as a precondition for a company's success. CIR offers an effective way in disseminating corporate information that can attract a wider range of national and international investors. The objective of this study is to investigate the nature and extent of CIR from the Malaysian perspective. A CIR index of 41 CIR attributes was developed for 380 Malaysian companies listed on the main market and the ACE Market of Bursa Malaysia. Data was analyzed using a descriptive statistical technique. From this sample, over three out of four companies have websites and are practicing CIR. The extent of CIR is discussed based on the industry type and specific CIR items. Our findings provide a better understanding of the level of CIR by these companies, towards encouraging more practices in the future. This study also contributes to the internet reporting literature in Malaysia. © Medwell Journals, 2016.